Contested organizational change and accounting in trials of incompatibility. (December 2019) - Christensen, Mark; Skærbæk, Peter; Tryggestad, Kjell
Abstract: This paper is about the role of accounting in making decisions about contested organizational change. We study how two strategic options emerged and were valued differently in a protracted case regarding sourcing by the Danish Defence Force. Drawing on Actor-Network Theory we show how the two strategic options emerged and were pitted against each other in what Callon describes as 'trials of strength'. The contribution of the paper is in three actions: First, it develops the concept of 'trial of strength' for accounting and organizational research by showing that extant literature can be enhanced with the conceptualization of a typology of trials that distinguishes between prototype trials and trials of incompatibility. Second, it shows that accounting inscriptions may play changing roles which we label 'versatile' when forged in the contested circumstances and resultant pressure of a trial of incompatibility. Third, it highlights how accounting inscriptions take part in (re)formulating, evaluating and advancing mutually exclusive reform options in a series of trials of strength involving both a prototype trial and trials of incompatibility. In addition to the frequency, number and intensity of the inscriptions there appears to be an increased prospect of unfaithful behavior by some inscriptions. This work also has implications for governmentality theorization and processual views of outsourcing decision making - as well as its paradoxical outcomes.